Non-dissociative single-electron ionization of diatomic molecules - Erbsen, Wes Corbin (Kansas State University, 2013)
Over the past four decades, the single-electron ionization of atoms has been a subject of great interest within the ultra-fast community. While contemporary atomic ionization models tend to agree well with experiment across a wide range of intensities (10[superscript]13-10[superscript]15 W/cm[superscript]2), analogous models for the ionization of molecules are currently lacking in accuracy. The deficiencies present in molecular ionization models constitute a formidable barrier for experimentalists, who wish to model the single-electron ionization dynamics of molecules in intense laser fields. The primary motivation for the work presented in this thesis is to provide a comprehensive data set which can be used to improve existing models for the strong-field ionization of molecules. Our approach is to simultaneously measure the singly-charged ion yield of a diatomic molecule paired with a noble gas atom, both having commensurate ionization potentials. These measurements are taken as a function of the laser intensity, typically spanning two orders of magnitude (10[superscript]13-10[superscript]15 W/cm[superscript]2). By taking the ratio of the molecular to atomic yields as a function of laser intensity, it is possible to "cancel out" systematic errors which are common to both species, e.g. from laser instability, or temperature fluctuations. This technique is very powerful in our ionization studies, as it alludes to the distinct mechanisms leading to the ionization of both molecular and atomic species at the same intensity which are not a function of the experimental conditions. By using the accurate treatments of atomic ionization in tandem with existing molecular ionization models as a benchmark, we can use our experimental ratios to modify existing molecular ionization theories. We hope that the data procured in this thesis will be used in the development of more accurate treatments describing the strong-field ionization of molecules.
Keywords: Ionization; Diatomic molecules; Molecular ionization; Femtosecond; Ultra-fast; Physics (0605)